Asserting citizenship: Muslim women's experiences with the hijab in Canada. (September 2016) - Rahmath, Sabah; Chambers, Lori; Wakewich, Pamela
Abstract: In Canada, hijab wearing Muslim women have increasingly faced discrimination in the post 9–11 era. In this study, we investigate Muslim women's experiences with the hijab and how they are viewed as the "other" in a multicultural country like Canada. Interviews were conducted with twenty-six Muslim women who describe their experiences with the hijab. The study focuses on how the hijab is perceived in public and how experiences with discrimination have motivated Muslim women to reclaim their voices in a space that perceives Muslim women to be oppressed. Thematic network analysis of the data revealed three central themes: religiosity, societal prejudice and internal struggle. Discrimination was experienced by all participants and internal struggles resulted in resolution techniques that helped in mitigating negative experiences. Highlights: The study investigates why Muslim women veil in Canada, how they face discrimination, and how experiences have shaped their views on the hijab. Societal racism and the perception of the self were found to be dominating factors in how Muslim women described the hijab. Muslim women face several stereotypes and are active in eradicating misconceptions about Muslim women.